A kölcsönösségen alapuló géphasználati formák megvalósíthatóságának kérdései a Dél-Dunántúl régióban - Tóthné Heim, Lívia (Acta Scientiarum Socialium, 2011)
One of the determinations of agricultural growth in countries with developed economy is the capital expenditure which has influence on manpower, and the development of technology act upon the development of the quality of manpower. The economic crisis experienced nowadays brings focus on the situation of our agri-culture with prestigious traditions. Despite the struggle of agricultural profession in decades, the solution how to turn the farmers to the direction of economized farming has not revealed yet. The most plausible resolution would seem to be the adaptation of the existing and well operating models of countries with well-developed agriculture in the European Union. In the 1990’s there were attempts to execute the models men-tioned above, yet the experiment failed of success. In sight of the present mechanized farming in the Southern Transdanube Region this study is searching for the answers how the farmers concerned - as members of companies or associations or co-operative societies based on correlation – could take advantage of reductions of the operational costs.
Keywords: mechanized farming; mechanization; operational costs; well-operating models; collective machine usage